2023
DOI: 10.1101/2023.06.17.545416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unveiling consistency in flexibility: the role of reward and cognitive control in moral decisions

Abstract: Moral decisions are multifaceted with two essential aspects, flexibility and consistency. However, the interaction between these two and the underlying mechanisms is rarely studied. Here, we combined mouse-tracking and functional magnetic resonance imaging (fMRI) together in a value-based moral decision task, which allows us to quantify accumulative history responses as self-consistency. Using a multi-attribute time-dependent drift-diffusion model (tDDM), we disentangled the role of consistency and self-intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 139 publications
1
5
0
Order By: Relevance
“…These results suggest that the interaction between DLPFC, a key component in cognition control and dishonesty 50 , and lTPJ which involves guilt processing 83,84 and self-image processing 50 , plays a crucial role in predicting the extent of metacognition change following dishonest behavior. Consistent with previous studies, moral versus immoral decisions are driven by both rewards and self-image 33,[85][86][87] . Dishonesty involves cognitive-control related brain regions like DLPFC and anterior cingulate cortex (ACC).…”
Section: Dlpfc Connectivity In Moral Decision-making Predicts Metacog...supporting
confidence: 89%
See 4 more Smart Citations
“…These results suggest that the interaction between DLPFC, a key component in cognition control and dishonesty 50 , and lTPJ which involves guilt processing 83,84 and self-image processing 50 , plays a crucial role in predicting the extent of metacognition change following dishonest behavior. Consistent with previous studies, moral versus immoral decisions are driven by both rewards and self-image 33,[85][86][87] . Dishonesty involves cognitive-control related brain regions like DLPFC and anterior cingulate cortex (ACC).…”
Section: Dlpfc Connectivity In Moral Decision-making Predicts Metacog...supporting
confidence: 89%
“…However, the current reward only affected future consistency in the next run, so current reward and current consistency could be viewed as two independent variables. Previous study 33 showed that both consistency and reward affected the dishonesty responses, we plotted the dishonesty probability as the function of reward and consistency, which was displayed in Figure S4D. This suggested that the participants considered both reward and consistency when they chose to lie or not in the IST.…”
Section: Memory Accuracy and Transformed Confidence Declined After Re...mentioning
confidence: 83%
See 3 more Smart Citations